PICTORICAL WARNING PADA KEMASAN ROKOK: KOMUNIKASI PERSUASIF DALAM KAMPANYE KESEHATAN - Negoro, Sherly Hindra (Informasi, 2017)
Smoking has became the serious problem which always to be the classical dynamic of health communication’s field. Through health campaign by using pictorical warning in cigarette packs, Indonesian Government has priority to reduce the number of smokers in Indonesia. Pictorical warning in cigarette packs was regard as one of communication strategic for implementing. Health campaign has outcome that could change the health behavior for the persuadee. Visualization by using image becomes persuasive communication tools cigarette packs as the communication media. EPPM model was used to analysis this case. This paper was using literature study to understand this problem.